AhR Ligands Differentially Regulate miRNA-132 Which Targets HMGB1 and to Control the Differentiation of Tregs and Th-17 Cells During Delayed-Type Hypersensitivity Response - Abdulla, Osama A.; Neamah, Wurood; Sultan, Muthanna; Chatterjee, Saurabh; Singh, Narendra; Nagarkatti, Mitzi; Nagarkatti, Prakash (Frontiers in Immunology, 2021)
Aryl hydrocarbon receptor (AhR), is a transcription factor and an environmental sensor that has been shown to regulate T cell differentiation. Interestingly, AhR ligands exert varying effects from suppression to exacerbation of inflammation through induction of Tregs and Th-17 cells, respectively. In the current study, we investigated whether the differential effects of AhR ligands on T cell differentiation are mediated by miRNA during delayed type hypersensitivity (DTH) reaction against methylated Bovine Serum Albumin (mBSA). Treatment of C57BL/6 mice with TCDD attenuated mBSA-mediated DTH response, induced Tregs, decreased Th-17 cells and caused upregulation of miRNA-132. TCDD caused an increase several Treg subsets including inducible peripheral, natural thymic, and Th3 cells. In addition, TCDD increased TGF-β and Foxp3 expression. In contrast, treating mice with FICZ exacerbated the DTH response, induced inflammatory Th17 cells, induced IL-17 and RORγ. Analysis of miRNA profiles from draining lymph nodes showed that miR-132 was upregulated in TCDD group and downregulated in FICZ group. Transfection studies revealed that miRNA-132 targeted High Mobility Group Box 1 (HMGB1). Downregulation of HMGB1 caused an increase in FoxP3+ Treg differentiation and suppression of Th-17 cells while upregulation of HMGB1 caused opposite effects. Moreover, TCDD was less effective in suppressing DTH response and induction of Tregs in mice that were deficient in miR-132. In summary, this study demonstrates that TCDD and FICZ have divergent effects on DTH response and T cell differentiation, which is mediated through, at least in part, regulation of miRNA-132 that targets HMGB1.